Analysis of the Influence of Work Discipline, Work Motivation, and Job Training on Employee Job Performance at PT PLN UP3 South Surabaya - Natazya, Arum; Farida, Siti Ning (PT. Riset Press International, 2025)
This study evaluates the influence of work discipline, work motivation, and job training on employee performance at PT PLN UP3 Surabaya Selatan. This study used a quantitative approach with a survey method involving 70 employees who were randomly selected as respondents. Data was collected by distributing questionnaires to measure the level of work discipline, work motivation, training received, and employee performance. The results showed that, simultaneously, the three variables of work discipline, work motivation, and job training significantly influence employee performance. However, the partial analysis results revealed that only work discipline and job training significantly impacted employee performance. In contrast, work motivation does not show a significant influence when analyzed separately. This indicates that at PT PLN UP3 Surabaya Selatan, work discipline and training factors are more influential on employee performance than work motivation. This research also indicates that employee performance is strongly influenced by how companies manage and strengthen work discipline and provide relevant and effective training programs.